PENINGKATAN KEMAMPUAN BERHITUNG ANAK MELALUI STIK ANGKA USIA ANAK 5-6 TAHUN DI PAUD CEMERLANG DESA SELASIH KABUAPATEN KAUR PROVINSI BENGKULU - Zalna; Rismareni Pransiska; Vivi Anggraini; Tisna Syafnita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Numeracy is a basic competency that needs to be developed in early childhood as part of cognitive development. Based on initial observations at the Cemerlang Early Childhood Education Center (PAUD) in Selasih Village, Kaur Regency, Bengkulu Province, the numeracy skills of Group B children aged 5–6 years old are still low. This study aims to improve children's numeracy skills through the application of number sticks in learning activities. The study used a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, implemented in two cycles, including planning, implementation, observation, and reflection. The study subjects consisted of 10 children in Group B: 4 boys and 6 girls. Data were collected through observation, performance tests, and documentation, then analyzed descriptively using quantitative and qualitative methods. The results showed that the use of number sticks gradually improved children's numeracy skills. The learning completion rate reached 30% at the initial stage, then increased to 60% in Cycle I and reached 90% in Cycle II. This improvement was evident in the children's ability to recognize number symbols, count objects, connect quantities with number symbols, and complete simple addition calculations. The research findings indicate that number sticks can be used as an effective learning alternative to develop early childhood numeracy skills. Furthermore, the results achieved exceeded the established success indicator of 75%.